Genetic Characterization of Maize Kisar Var. Kuning Genjah and Maize Var. Bisi-II-Hibrida Based On Molekular RAPD Marker - Elizabeth C. Berhitu; Adriana Hiariej; Cecilia A. Seumahu (Agrotech Journal, 2019)
The variety of maize in Southwest Maluku (MBD) has an ability to grow in the extremely dry land, especially at Kisar island, because those areas were dominated by dry land. Dry resistance very useful to be used for genetical characterization in order to provide accurate data about the character of local maize Kisar var. Kuning Genjah. To identify the characteristics at the genome level of this local maize variety, one of the molecular methods that can be applied was RAPD molecular method. The advantage of the RAPD marker is it's technically simpler and fast in testing, does not require DNA sequence information, hence this marker becomes widely used, it only requires a small sample of DNA, the primary is commercially available and does not use radioactive compounds. The aim of this study was to find out the bands profile that has the potential to be used as a marker of dry resistance. The method applied was RAPD (Random Amplified Polymorphic DNA) using OPA-02, OPA-07, and OPC-12 primers and produces 22 DNA bands. The measurement of bands by estimating the molecular weight based on marker exponential regression. The polymorphic percentage was 90.9% between var. Kuning genjah and var. BIZI-II-Hybrid. The percentage of polymorphism showed the potential of bands that can be used as molecular markers for markers of dry resistance that can be utilized in plant breeding